Free thyroxine within the normal reference range predicts risk of atrial fibrillation. (17th November 2019) - Anderson, Jeffrey L.; Jacobs, Victoria; May, Heidi T.; Bair, Tami L.; Benowitz, Barry A.; Lappe, Donald L.; Muhlestein, Joseph B.; Knowlton, Kirk U.; Bunch, T. Jared
Abstract: Introduction: Hyperthyroidism is a known precipitating factor for atrial fibrillation (AF). However, recent reports have suggested an increased risk of AF with free thyroxine (fT4) levels even within the upper reference (normal) range. We sought to test whether higher fT4 levels within the reference range are associated with an increased risk of AF. Methods and Results: All patients in the Intermountain Healthcare electronic medical record database with an fT4 level not on thyroid medication were included. The reference range of fT4 was divided into quartiles (Q), and associations with prevalent and incident AF were assessed by multivariable regression. Similar analyses were performed for thyroid stimulating hormone (TSH) and total and free T3. A total of 174 914 patients were included and followed for 7.0 ± 4.9 years. Of these, 7.4%, 88.4%, and 4.2% had fT4 levels below, within, and above the reference range. As expected, prevalent AF was greater with elevated fT4. However, gradients also were noted within the reference range, comparing Q4 to Q1, for prevalent AF (adjusted odds ratio 1.4, P < .0001) and incident AF (adjusted hazard ratio 1.16, P < .0001). In contrast, no relationship with AF prevalence and incidence was noted for total and free T3 within their reference ranges, and the pattern for TSH was uninformative. Conclusion: Higher fT4 levels within the reference range were associated with an increased prevalence and incidence of AF. These findings in a large dataset prospectively validate earlier reports and may have important implications, including a redefinition of the normal range and fT4 targets for replacement therapy.